Experimental Study on Wear Behaviors of TBM Disc Cutter Ring in Hard Rock Conditions. Issue 5 (3rd September 2018) - Lin, Laikuang; Xia, Yimin; Mao, Qingsong; Zhang, Xuhui
ABSTRACT: To improve the wear resistance of disc cutters for tunnel boring machines (TBMs), this study is devoted to investigating the effects of rocks and cutter ring properties on the wear behaviors of disc cutters and the matching characteristics between the cutter ring properties and hard rocks. Cutter–rock wear tests were performed and the results show that the cutter ring properties and rock types significantly affect the cutter ring wear. The mass losses of cutter ring samples sliding against different types of hard rock are different and vary with the cutter ring properties because of the discrepancies in loads, vibrations, rock properties, and transition of the wear mechanisms. Finally, matching characteristics between the cutter ring properties and hard rocks are revealed.